Gambaran Stres Akademik Mahasiswa dalam Pembelajaran Jarak Jauh - Eka Apristian Pantu (Fakultas Dakwah UIN KHAS Jember, 2026)
The uneven quality of internet networks in different regions of Indonesia has resulted in some individuals being less skilled in implementing online learning, which in turn contributes to academic stress. This study aims to measure students’ academic stress in online learning. A descriptive quantitative approach was employed, involving 273 students from Gorontalo who engaged in online learning. Data were collected through an online questionnaire distributed via a link and analyzed using SPSS with mean analysis. The findings revealed that students’ academic stress in online learning was at a moderate level. Similar results were found in the aspects of academic expectations and issues related to learning and examinations. The only aspect that showed a high score was academic self-perception. The findings indicate that online learning is not an appropriate substitute for face-to-face learning, particularly in regions with inadequate internet access.